Comparative Evaluation of Algae, Yeast, and Mixed Diets on Growth Performance and Proximate Composition of Artemia franciscana in a 30-Day Culture System - Owais, Muhammad (Iraqi Journal of Aquaculture, 2025)
This study investigated the effects of dietary supplementation with microalgae (Chlorella vulgaris), yeast (Saccharomyces cerevisiae), and a 1:1 combination of both on the growth performance and proximate composition of Artemia franciscana over a 30-day culture period. Four feeding treatments were evaluated: a control (natural seawater microbial load), yeast-only (2 g/L), algae-only (2 g/L), and a mixed diet (1 g/L yeast + 1 g/L algae). The results revealed that dietary treatment significantly influenced all measured parameters (p ≤ 0.05). The mixed diet group achieved the highest growth performance, with a final length of 7.4 ± 0.4 mm, biomass of 7.5 ± 0.3 mg, weight gain of 300.5 ± 9.6%, and survival rate of 88.4 ± 2.6%. Algae-fed Artemia also showed notable improvement (final length: 6.7 ± 0.5 mm; biomass: 6.8 ± 0.4 mg; weight gain: 270.3 ± 11.2%; survival: 81.1 ± 2.3%), followed by the yeast group (final length: 6.3 ± 0.3 mm; biomass: 6.3 ± 0.3 mg; weight gain: 254.5 ± 10.6%; survival: 78.7 ± 2.7%). The control group recorded the lowest values across all metrics, with a final biomass of 1.7 ± 0.1 mg and survival of 52.4 ± 3.5%. Proximate composition analysis further confirmed the nutritional benefits of the mixed diet, which produced the highest crude protein (53.7 ± 1.2%) and lipid content (15.4 ± 0.3%) with reduced ash (11.3 ± 0.6%) and moisture levels (75.3 ± 0.5%). These findings demonstrate that a combined yeast–algae diet provides complementary nutrients that enhance Artemia growth and nutritional quality. These results highlight the potential of mixed yeast–algae diets as a sustainable and cost-effective strategy for producing nutritionally enriched Artemia in aquaculture systems.